Analisis tingkat kepemilikan aset perempuan di Kecamatan Pengasih Kabupaten Kulon Progo - Amalia, Nurisqi; Aini Yuniyarti, Nur (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
Women’s problems can be resolved through ownership of the assets. Through descriptive statistical methods, composite score, and ordinal probit regression, this study aims to determine the age and education profile of women and her husband, the profile of women’s asset ownership, as well as the effect of that profile on women’s asset ownership in Karangsari Village, Pengasih District, Kulon Progo Regency. The results showed that the majority of women and her husband were between 51 and 64 years old. The percentage of women at that age was 26.7% and her husband 27.27%. in terms of education, the majority of both have high school education. based on the category of ownership of the asset, more than half of the population is in the medium (intermediate) category. The influence of age and education shows that only the women education variable has an effect on asset ownership.